PRODUKTIVITAS, INVESTASI SUMBERDAYA MANUSIA, INVESTASI FISIK, KESEMPATAN KERJA TERHADAP KEMISKINAN DAN PERTUMBUHAN EKONOMI DI INDONESIA - Aimon, Hasdi (Jurnal Kajian Ekonomi, 2012)
ABSTRACT This study is focused on productivity, human resources  investment, phisical investment and  employment to proverty and economic growth  in  Indonesia. The proverty  is influenced by  education investment, health investment,  productivity and economic growth. On the other hand, the economic growth part is affected by productivity,  phisical investment,  employment  and  proverty. From econometric study, we found that proverty and economic growth give causality and contribute significantly. The data series was taken from 1980-2009. Simultaneous model 2SLS is used to analyze  education investment, health  investment, productivity, phisical investment, employment, proverty and economic growth coefficients size. Before future analysis, we also checked stationary test, co-integration test and causalities between  proverty  and  economic growth. We conclude that  the government need to increase incentive in public sector and riel sector in order to increase investment and economic. Therefore, it can decrease proverty rate and increase economic growth in Indonesia. Keyword: Human resources investment, Phisical investment, Productivity, Proverty and Economic growth.